2012
DOI: 10.1016/j.jclepro.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Freeze/thaw protection of concrete with optimum rubber crumb content

Abstract: This research looks at utilising an optimum quantity of rubber crumb as an air entraining admixture in concrete, thus providing maximum freeze thaw protection and maximum strength.Microscopic and chemical analysis was carried out on the rubber sample to investigate how rubber crumb entrains air and reacts with the surrounding concrete. The work contained two pilot studies that informed the main test methodology. The pilot studies examined the air content/compressive strength relationship (1) and freeze/thaw cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 18 publications
3
60
0
Order By: Relevance
“…Investigations into the performance of CRC in different environments found that the use of air entraining admixtures increases the durability against freeze thaw action [30][31][32][33]. A study into the compressive behaviour of CRC subjected to excessive heat [15] (25°C to 600°C) demonstrated a significant improvement in energy absorption particularly with smaller grades of rubber and lower fine aggregate replacements.…”
Section: Crc Acoustic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into the performance of CRC in different environments found that the use of air entraining admixtures increases the durability against freeze thaw action [30][31][32][33]. A study into the compressive behaviour of CRC subjected to excessive heat [15] (25°C to 600°C) demonstrated a significant improvement in energy absorption particularly with smaller grades of rubber and lower fine aggregate replacements.…”
Section: Crc Acoustic Propertiesmentioning
confidence: 99%
“…Three more were tested following freezing for 24 hours at -15 0 C with the remainder subject to normal laboratory conditions (15±5 0 C) to assess the acoustic performance of CRC in these conditions as its improved durability in these environments has been previously reported [32,38].…”
Section: Sound Insulationmentioning
confidence: 99%
“…segregation and bleeding) of the fresh RuC mix has to be taken into account. Due to the relatively low density of rubber compared to mineral aggregates and cement, RuC cylinders with inadequate mix proportioning, consolidation or handling can exhibit a high concentration of rubber at the top upon vibration [20,21]. The increase in porosity and entrapped air content (up to 30% at 25% rubber replacement by volume [20]) is conceivably the main reason behind the poor fresh performance of RuC [22].…”
Section: Introductionmentioning
confidence: 99%
“…To improve rubber-cement paste chemical/physical bonding [18], several rubber pre-treatments have been investigated such as washing with water [21,35,42], polyvinyl alcohol [43], NaOH [13,41,44,45], Ca(OH) 2 [46], silane coupling agents [47], organic sulphur compounds [48] or acid [40], as well as partial oxidation of the rubber surface [49], exposure to UV radiations [50] or pre-coating with cement [51], mortar [26], silica fume [39], limestone [52] or sand [45]. Despite some success in rubber pre-treatments (strength increase in the range of 3-40% [18,26,41,51,52]), results are often scattered and inconclusive, particularly when mixes with pre-treated rubber are not compared to mixes with as-received rubber [35,42].…”
mentioning
confidence: 99%
See 1 more Smart Citation